Conversations in couple relationships: a trustful foundation when making future parenthood “real” - Flisbäck, Marita (Frontiers in Sociology, 2024)
Sociologists often argue that communication in long-term couple relationships is the basis on which expectations, trust, and equality are created in contemporary society. However, what is the role of these everyday conversations in uncertain life situations such as expecting one’s first child? This article examines concerns reported by prospective Swedish parents in order to explain the role of communication to alleviate these. Concerns, related to the formation of new relationships with one’s partner, oneself, and one’s future child, are mitigated by referring to the couple’s “good” communication. In the present prenatal situation, the communication pattern (established in the past) seems to serve three functions in mitigating future concerns: (1) the communication generates a trust capital in the relationship, allowing the couple to venture into the uncertain future, (2) the communication makes social perceptions of family life “real” by constructing a common nomos that is internalized in the individual as an existential motto, and (3) the communication legitimizes family practices as democratic when referring to future plans as emerging from responsive and consensual dialogs. In the article it is emphasized that welfare policy needs to be based on an existential legitimacy, often developed in couple conversations, and particularly shaped in life situations characterized by change. However, the stability offered at the conversational micro level may simultaneously prevent macro level changes, a complexity that needs to be considered when developing a gender equality policy that is to resonate with people’s existential meaning making. With the aim of consensus, and the means of balancing conflicts, there is a risk that the conversation will consolidate the interests of the stronger party. In this way, the responsive conversations in long-term relationships may consolidate gender inequality and counteract the welfare policy goal of equalizing power relationships.